Epileptic brain imaging by source localization CLARA supported by ictal-based semiology and VEEG in resource-limited settings - Al-Bakri, Amir F.; Muslim, Ahmed Tahseen; Faraj, Moneer K.; Esam Matti, Wamedh; Vilimkova Kahankova, Radana; Mikolajewski, Dariusz; Karwowski, Waldemar; Kawala-Sterniuk, Aleksandra (Frontiers in Neuroinformatics, 2025)
IntroductionAccurate localization of the epileptogenic zone is essential for surgical treatment of drug-resistant epilepsy. Standard presurgical evaluations rely on multimodal neuroimaging techniques, but these may be limited by availability and interpretive challenges. This study aimed to assess the concordance between zones identified by ictal semiology and a novel distributed electrical source localization technique, CLARA, and to evaluate their impact on postsurgical outcomes.MethodsThis retrospective study included 16 patients with at least three recorded seizures. Ictal semiology was analyzed subjectively using video electroencephalography (VEEG) by a multidisciplinary team of neurologists, neurophysiologists, and radiologists, who determined the presumed epileptogenic zone at the lobar level. CLARA was subsequently applied to identify the computed zone based on ictal and/or interictal biomarker activities. The concordance between the presumed and computed zones was assessed qualitatively. Postsurgical outcomes were examined in relation to the extent of resection of the CLARA-defined zones.ResultsAmong thirteen patients with sufficient data for analysis, qualitative comparison showed 77% concordance and 23% partial concordance between the presumed and computed zones. Postsurgical follow-up revealed seizure freedom in one patient with cavernoma following complete resection of the CLARA-defined zone. In contrast, patients with incomplete resection of this region continued to experience seizures.DiscussionThe findings support the potential value of CLARA as an adjunctive neuroimaging technique in the presurgical evaluation of epilepsy. By providing an additional layer of verification, CLARA may improve the accuracy of epileptogenic zone localization when used alongside established modalities such as PET, SPECT, fMRI, and MRI. Its adaptability and lower resource requirements suggest particular utility in centers with limited access to advanced medical equipment and specialized personnel. Broader implementation of CLARA could enhance presurgical decision-making and contribute to improved surgical outcomes for epilepsy patients.